Head‐to‐head comparison of contemporary heart failure risk scores. (1st October 2021) - Codina, Pau; Lupón, Josep; Borrellas, Andrea; Spitaleri, Giosafat; Cediel, Germán; Domingo, Mar; Simpson, Joanne; Levy, Wayne C.; Santiago‐Vacas, Evelyn; Zamora, Elisabet; Buchaca, David; Subirana, Isaac; et al.
Abstract: Aims: Several heart failure (HF) web‐based risk scores are currently used in clinical practice. Currently, we lack head‐to‐head comparison of the accuracy of risk scores. This study aimed to assess correlation and mortality prediction performance of Meta‐Analysis Global Group in Chronic Heart Failure (MAGGIC‐HF) risk score, which includes clinical variables + medications; Seattle Heart Failure Model (SHFM), which includes clinical variables + treatments + analytes; PARADIGM Risk of Events and Death in the Contemporary Treatment of Heart Failure (PREDICT‐HF) and Barcelona Bio‐Heart Failure (BCN‐Bio‐HF) risk calculator, which also include biomarkers, like N‐terminal pro B‐type natriuretic peptide (NT‐proBNP). Methods and results: A total of 1166 consecutive patients with HF from different aetiologies that had NT‐proBNP measurement at first visit were included. Discrimination for all‐cause mortality was compared by Harrell's C‐statistic from 1 to 5 years, when possible. Calibration was assessed by calibration plots and Hosmer–Lemeshow test and global performance by Nagelkerke's R 2 . Correlation between scores was assessed by Spearman rank test. Correlation between the scores was relatively poor (rho value from 0.66 to 0.79). Discrimination analyses showed better results for 1‐year mortality than for longer follow‐up (SHFM 0.817, MAGGIC‐HF 0.801, PREDICT‐HF 0.799, BCN‐Bio‐HF 0.830). MAGGIC‐HF showed the best calibration, BCN‐Bio‐HF overestimated risk while SHFM and PREDICT‐HF underestimated it. BCN‐Bio‐HF provided the best discrimination and overall performance at every time‐point. Conclusions: None of the contemporary risk scores examined showed a clear superiority over the rest. BCN‐Bio‐HF calculator provided the best discrimination and overall performance with overestimation of risk. MAGGIC‐HF showed the best calibration, and SHFM and PREDICT‐HF tended to underestimate risk. Regular updating and recalibration of online web calculators seems necessary to improve their accuracy as HF management evolves at unprecedented pace. Abstract : Head‐to‐head comparison of contemporary heart failure risk scores. ACEI, angiotensin‐converting enzyme inhibitor; ARB, angiotensin II receptor blocker; ARNI, angiotensin receptor–neprilysin inhibitor; BB, beta‐blocker; CRT, cardiac resynchronization therapy; ICD, implantable cardioverter‐defibrillator; HFmrEF, heart failure with mildly reduced ejection fraction; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with reduced ejection fraction; MRA, mineralocorticoid receptor antagonist.